Improving Learning Outcomes of Islamic Religious Education for Elementary School Students with the Application of the Talking Stick Learning Model - Wantini, Wantini; Waharjani, Waharjani; Wijayanti, Clara Shinta; Suyatno, Suyatno (Institut Agama Islam Negeri Imam Bonjol Padang, 2023)
This study aims to analyse the improvement of Islamic religious education learning outcomes for elementary school students by applying the Talking Stick learning model. A Achieving the target of learning is the main goal of an educator to his students. In fact, there are not a few educators who have not fully implemented how to learn effective and fun and still stick only with classical methods. There are quite a few choices of learning models, one of which is the Talking Stick. This research was conducted using the Systematic Literature Review method which was carried out by reviewing, analysing, and drawing conclusions based on relevant articles that were screened and selected systematically. In this study, we will discuss efforts to improve elementary school student learning outcomes by applying the Talking Stick learning model. Learning outcomes by applying the Talking Stick learning model, namely, the experimental class with the Talking Stick model immediately showed significant differences in learning outcomes in the first cycle compared to before the implementation of Talking Stick. Several other studies on the implementation of the Talking Stick model were carried out for 2 to 3 cycles and then there was a significant difference in results from before the implementation of the Talking Stick learning model.